2016
DOI: 10.5194/acp-16-4867-2016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and meteorological influences on the lifetime of NO<sub>3</sub> at a semi-rural mountain site during PARADE

Abstract: Abstract. Through measurements of NO2, O3 and NO3 during the PARADE campaign (PArticles and RAdicals, Diel observations of mEchanisms of oxidation) in the German Taunus mountains we derive nighttime steady-state lifetimes (τss) of NO3 and N2O5. During some nights, high NO3 (∼ 200 pptv) and N2O5 (∼ 1 ppbv) mixing ratios were associated with values of τss that exceeded 1 h for NO3 and 3 h for N2O5 near the ground. Such long boundary-layer lifetimes for NO3 and N2O5 are usually only encountered in very clean/unre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 57 publications
3
76
1
Order By: Relevance
“…As reported previously for this site (Crowley et al, 2010;Phillips et al, 2012;Sobanski et al, 2016) local emissions result in high variability in NO x with NO 2 usually between ∼ 0.5 and 10 ppbv but with excursions up to ∼ 20 ppbv. Daytime maxima for NO were between ∼ 0.5 and 2 ppb and ozone levels were between 20 and 70 ppbv.…”
Section: Particle Characteristicsmentioning
confidence: 59%
See 1 more Smart Citation
“…As reported previously for this site (Crowley et al, 2010;Phillips et al, 2012;Sobanski et al, 2016) local emissions result in high variability in NO x with NO 2 usually between ∼ 0.5 and 10 ppbv but with excursions up to ∼ 20 ppbv. Daytime maxima for NO were between ∼ 0.5 and 2 ppb and ozone levels were between 20 and 70 ppbv.…”
Section: Particle Characteristicsmentioning
confidence: 59%
“…The Kleiner Feldberg (825 m above sea level) sits within the Taunus range approximately 30 km NW of Frankfurt am Main, Germany. The site, which may be described as rural with anthropogenic impact from local industrial/population centres, is described in more detail by Wobrock et al (1994), Handisides (2001), Crowley et al (2010) and Sobanski et al (2016). It is ≈ 400 km away from the nearest (North Sea) coastline.…”
Section: Parade Field Sitementioning
confidence: 99%
“…The mean nighttime value of 25 k OTG was ≈ a factor ten lower at 0.11 s -1 , the daytime mean even lower at 0.04 s -1 . Broadly speaking, the nighttime NO 3 lifetimes during IBAIRN were very short (≈ 10 s on average) compared to previous indirect, ground level measurements in other locations where several groups have reported lifetimes of hundreds to thousands of seconds (Heintz et al, 1996;Allan et al, 1999;Geyer et al, 2001;Aldener et al, 2006;Ambrose et al, 2007;Brown et al, 2009;Crowley et al, 2010;Crowley et al, 2011;Sobanski et al, 2016b Figure 3b illustrates the dependence of k OTG on wind direction. Air masses from the northern sector were generally associated with lower reactivity (<0.2 s -1 ) whereas all incidents of reactivity larger than 0.3 s -1 were associated with air masses from the SE sector.…”
Section: No 3 Reactivity and Nighttime Loss Of Omentioning
confidence: 80%
“…The first method may break down when stationary state is not achieved (Brown et al, 2003). For example, Sobanski et al (2016b) observed much lower stationary-state loss rates of NO 3 compared to those calculated from measured VOC mixing ratios in a forested /urban location and concluded that this was mainly the result of sampling from a low-lying residual layer 15 with VOC emissions that were too close to the sampling point for NO 3 concentrations to achieve stationary-state. The second method relies on comprehensive measurement and accurate quantification of all VOCs that react with NO 3 , which, in a chemically complex environment such as a forest, may not always be possible.…”
mentioning
confidence: 96%
“…The references to the various measurements are indicated in Table 1. C2-C4 alkanes and alkenes (ethane: C2H6, ethene: C2H4, propane: C3H8, propene: C3H6, butane: C4H10 (i and n), butene: C4H8 (c and t) were measured with a time resolution of 60 min and the mixing ratio represents an average over a sampling period of 20 min 15 (Sobanski et al, 2016). Photolysis frequencies were obtained by a CCD Spectroradiometer (Metcon GmbH) operating at 275-640 nm with a 2-π integrating hemispheric quart dome.…”
mentioning
confidence: 99%